Too bored for sports? Adaptive and less-adaptive latent personality profiles for exercise behavior. (March 2021) - Wolff, Wanja; Bieleke, Maik; Stähler, Johanna; Schüler, Julia
Abstract: Physical exercise is an effective tool for improving public health, but the general population exercises too little. Drawing on recent theorizing on the combined role of boredom and self-control in guiding goal-directed behavior, we test the hypothesis that individual differences in boredom and self-control differentiate high from low exercisers. The role of boredom as a non-adaptive disposition is of particular interest, because research on boredom in sports is scarce. Here, we investigate the role of such individual differences in self-reported weekly exercise behavior (in minutes) in a sample of N  = 507 participants ( n  = 200 female, M age  = 36.43 (±9.54)). We used the robust variant of Mahalanobis distance to detect and remove n  = 51 multivariate outliers and then performed latent profile analysis to assess if boredom (boredom proneness; exercise-related boredom) and self-control (trait self-control; if-then planning) combine into identifiable latent profiles. In line with theoretical considerations, the Bayesian Information Criterion favored a solution with two latent profiles. One profile was characterized by higher-than-average exercise-related boredom and boredom proneness and lower-than-average self-control and if-then planning values. This pattern was reversed for the second profile. A one-sided Bayesian two-sample t -test supported the hypothesis that the first profile is associated with less exercise behavior than the second profile, BF = 16.93. Our results foster the notion of self-control and if-then planning as adaptive dispositions. More importantly, they point to an important role of boredom in the exercise setting: exercise-related boredom and getting easily bored in general are associated with less exercise activity. This is in line with recent theorizing on boredoms' and self-controls' function in guiding goal-directed behavior. Highlights: Boredom is linked with lower exercise levels. Self-control is linked with higher exercise levels. Boredom and self-control combine into more or less adaptive latent profiles. We provide a first self-report measure for exercise related boredom. Discrete achievement emotions like boredom need more research in the sports context.